The return of the forgotten: redescription and new data on the distribution of Acnemia sibirica Ostroverkhova, 1979 (Diptera: Mycetophilidae) - Subbotina, Elena; Maksimova, Yulia; Polevoi, Alexei (Zootaxa, 2024)
The description of Acnemia sibirica was published by G.P. Ostroverkhova in her 1979 monograph. The species, however, was mistakenly given as it had been described in 1978. Moreover, it was not explicitly indicated as a new species (except in the legend for the figure of male terminalia), and type specimens were not designated. Evidently, due to confusion with the original description, the species was not mentioned in the recent literature and was not included in the online taxonomic databases. Anyway, the name complies with the availability criteria according to the International Code of Zoological Nomenclature, and hence the species should be treated as Acnemia sibirica Ostroverkhova, 1979. The identity of the species can be reliably established based on the original figures by G.P. Ostroverkhova and on preserved slides. The species is here redescribed, and illustrations of the male terminalia for both type and new specimens are provided. Lectotype and paralectotypes are designated. New data on species’ distribution are reported.